Garbage enzyme pineapple waste hybrid (CA II) nanoflower (GPW-HNF) for VBR dye decolourisation - Joyce Cynthia, Jalani; Zatul Iffah, Mohd Arshad; Rohaida, Che Man; Chew, Few Ne; Shalyda, Md Shaarani; Siti Kholijah, Abdul Mudalip; Siti Zubaidah, Sulaiman (Universiti Kebangsaan Malaysia, 2025)
Victoria blue R (VBR) is a synthetic dye that resists natural degradation and poses an increasing threat to all forms of life. This research reports on the development of organic-inorganic hybrid nanoflowers using pineapple waste garbage enzyme (PGE) as the organic component and calcium (II) ions as the inorganic component for the decolourisation of VBR dye. The synthesised garbage enzyme pineapple waste-calcium (II) ions hybrid nanoflowers (GPW-hNFs) were characterised using BET, EDX, FTIR, FESEM, and XRD analyses. The optimum initial concentration of VBR dye, amount of nanoflower (NF), pH, sonication time, and temperature of GPW-hNFs were also studied. The results demonstrated that 0.10 g of nanoflower, pH 7.4, 30 minutes of sonication, and 37°C, with an initial dye concentration of 0.06 mg/mL were the optimal conditions to achieve a 90% decolourisation rate. Furthermore, GPW-hNFs offer a more sustainable solution for VBR dye decolourisation compared to LACCASE Y120, pineapple waste garbage enzyme (PGE), and hydrogen peroxide (H₂O₂). Overall, this study suggests that GPW-hNFs have the potential for real-world wastewater treatment applications.